(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to explore the relationship between the use of electronic games and social isolation among secondary school students in the city of Misrata. The study was designed using a descriptive-analytical approach, relying on the social survey method with a sample, due to its consistency with the nature of the topic. A non-probability convenient sample of 125 secondary school students was selected. Given that the study was conducted during the summer school holiday, questionnaires were distributed and collected from students gathering in parks, resorts, and tourist villages within the city, as these locations are the most attractive for students during the summer break. The study employed the Symbolic Interactionism Theory to interpret the relationship between students’ exposure to electronic games and their impact on social interaction patterns. This theoretical framework focused on analyzing how individuals perceive the meanings of electronic games and determining their reflections on the ways they communicate with their social environment. The study results outlined a set of conclusions related to its hypotheses, the most notable of which was the absence of a statistically significant correlation between the use of electronic games and interaction with friends, as well as the lack of a statistically significant correlation between electronic games and social mixing (socializing). On the other hand, a correlation was found between electronic games and family communication, in addition to a statistically significant relationship between electronic games and social withdrawal. Furthermore, the results revealed statistically significant differences in the relationship between electronic games and social mixing according to the participants’ gender variable, while no statistically significant differences were observed in aspects related to interaction with friends, family communication, or social withdrawal based on the respondents’ gender. Conclusively, the study presented a set of recommendations, the most important of which included enhancing awareness within families and educational institutions about the importance of using electronic games in a balanced manner, and calling for the expansion of field studies to include different age groups and various geographical areas.